Bovine Viral Diarrhea Virus and Related Pestiviruses - Bielefeldt-Ohmann, Helle (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The pestiviruses encompass some of the most economically important viral infections in the cattle, swine, and sheep industries worldwide. Discovered more than 70 years ago, bovine viral diarrhea virus (BVDV) and classical swine fever virus (CSFV) were long the main concern, but many new pestiviruses have emerged in recent years, which may also present additional threats to biosecurity and food safety. This issue brings together contributions from multiple disciplines - virology, immunology, veterinary clinical medicine, epidemiology, and pathology - on the subject of BVDV and related pestiviruses, and cover host-virus interactions, virus-cell interactions, cross-species transmission as well as the role of wildlife species as reservoirs of some of the pestiviruses.